Prevalence and Risk Factors of Emotional Mental Disorder Among University Students: A Cross-Sectional Study - Habibah, Umrohtul; Syakurah, Rizma Adlia; Aini, Syarifah; Ikhsan, Diyaz Syauki; Zulissetiana, Eka Febri (UIN Sunan Kalijaga, 2025)
Emotional mental health issues among university students have shown an increasing trend over time, reaching concerning levels when compared to the general population. Early detection is very important for the university as an early intervention to improve students’ mental health. This study used an analytic observational design with a cross-sectional approach. A total of 1564 students from 10 faculties of Sriwijaya University filled in the SRQ-29 questionnaire online via social media from January 2020 – 27 August 2020. The obtained data were analyzed using the Mann Whitney, Chi-Square, and Binary Logistic Regression Test with a significance value of p<0.05. As much as 56.6% of the students experienced symptoms of neurosis, 75.6% had symptoms of PTSD, 55% had psychotic symptoms, while 1.2% had symptoms of substance abuse. Students with a history of chronic disease are more susceptible to experience emotional mental disorders (86%). Gender, faculty, domicile, history of chronic disease and history of mental disorders in the family significantly affected emotional disorders (p <0.05). Universities need to provide mental health facilities that are managed by professionals and ensure the confidentiality of data in their environment.Permasalahan kesehatan mental emosional di kalangan mahasiswa menunjukkan kecenderungan yang semakin meningkat dari waktu ke waktu, bahkan pada tingkat yang mengkhawatirkan jika dibandingkan dengan populasi umum. Deteksi dini sangat penting bagi universitas sebagai intervensi dini untuk meningkatkan kesehatan mental mahasiswa. Penelitian ini menggunakan desain observasional analitik dengan pendekatan cross sectional. Sebanyak 1564 mahasiswa dari 10 fakultas Universitas Sriwijaya mengisi kuesioner SRQ-29 secara online melalui media sosial dari Januari 2020 – 27 Agustus 2020. Data yang diperoleh dianalisis menggunakan Mann Whitney, Chi-Square, dan Uji Regresi Logistik Biner dengan nilai signifikansi p<0,05. Sebanyak 56,6% siswa mengalami gejala neurosis, 75,6% mengalami gejala PTSD, 55% mengalami gejala psikotik, sedangkan 1,2% mengalami gejala penyalahgunaan zat. Mahasiswa dengan riwayat penyakit kronis lebih rentan mengalami gangguan mental emosional (86%). Jenis kelamin, fakultas, domisili, riwayat penyakit kronis dan riwayat gangguan jiwa dalam keluarga berpengaruh signifikan terhadap gangguan emosi (p<0,05). Perguruan tinggi perlu menyediakan fasilitas kesehatan jiwa yang dikelola secara profesional dan menjamin kerahasiaan data di lingkungannya.